Inotersen preserves or improves quality of life in hereditary transthyretin amyloidosis - Coelho, Teresa (2020)
Objective: To examine the impact on quality of life (QOL) of patients with hATTR amyloidosis with polyneuropathy treated with inotersen (Tegsedi™) versus placebo. Methods: Data were from the NEURO-TTR trial (ClinicalTrials.gov Identifier: NCT01737398), a phase 3, multinational, randomized, double-blind, placebo-controlled study of inotersen in patients with hATTR amyloidosis with polyneuropathy. At baseline and week 66, QOL measures-the Norfolk-QOL-Diabetic Neuropathy (DN) questionnaire and SF-36v2® Health Survey (SF-36v2)-were assessed. Treatment differences in mean changes in QOL from baseline to week 66 were tested using mixed-effect models with repeated measures. Responder analyses compared the percentages of patients whose QOL meaningfully improved or worsened from baseline to week 66 in inotersen and placebo arms. Descriptive analysis of item responses examined treatment differences in specific activities and functions at week 66. Results: Statistically significant mean differences between treatment arms were observed for three of five Norfolk-QOL-DN domains and five of eight SF-36v2 domains, with better outcomes for inotersen than placebo in physical functioning, activities of daily living, neuropathic symptoms, pain, role limitations due to health problems, and social functioning. A larger percentage of patients in the inotersen arm than the placebo arm showed preservation or improvement in Norfolk-QOL-DN and SF-36v2 scores from baseline to week 66. Responses at week 66 showed more substantial problems with daily activities and functioning for patients in the placebo arm than in the inotersen arm. Conclusion: Patients with hATTR amyloidosis with polyneuropathy treated with inotersen showed preserved or improved QOL at 66 weeks compared to those who received placebo.